Making movies with your iPhone : shoot, edit, and share from anywhere - Ben J Harvell (Ilex, 2012)
Making movies with your iPhone reveals the features that transform your trusty iPhone into a pro-quality video tool. From shooting documentary footage to full-length films, you can not only a record video on the iPhone, but edit and publish movies from it as well. With everything from accessories mand shooting advice to the best apps for editing and applying effects, this book is a must for everyone who wants to harness the power of their iPhone to make professional-quality movies, from the family filmmaker to the budding auteur. Read less